Certification, Forest Conservation, and Cattle: Theories and Evidence of Change in Brazil. Issue 3 (25th June 2014) - Newton, Peter; Alves‐Pinto, Helena Nery; Pinto, Luís Fernando Guedes
Abstract Voluntary certification programs for agricultural and forest products have been developed to improve the environmental and social sustainability of production processes. The new Sustainable Agriculture Network (SAN) cattle certification program aims to reduce deforestation in the cattle supply chain, with a focus on Brazil. Drawing on information from interviews with key actors in Brazil, this article discusses the mechanisms that may enable the SAN cattle program to achieve these goals and to avoid critiques that have been leveled at other commodity certification programs. The program sets higher standards for sustainability than any existing policy or incentive mechanism. Participation in the program may generate significant indirect financial and non‐financial benefits. The program may also influence the supply chain more widely: by demonstrating that certifiable, traceable, sustainable cattle production is viable; by "raising the bar" of sustainability standards through rigorous criteria; and by creating new markets and incentives. While the scaling up and impact of the SAN cattle program will depend in part on how it is supported or constrained by other interventions in the same sector, the program appears to be characterized by a rigorous program design that is necessary, if not sufficient, to catalyze reduced rates of forest loss.